Namūżaju Ikhtibārāt al-Lugah li al-Tarjamah al-‘Arabiyyah ‘alā Asāsi Nażariyyati Jean Piaget: The Model of Language Tests for Arabic Translation is Based on Jean Piaget's Theory - Mahmudi, Ihwan; Badriya, Iffatunnisail (Aphorisme: Journal of Arabic Language, Literature, and Education, 2023)
The need for translation test models is increasing every day, thus facilitating the learning process of translation and the creation of related exercises. The purpose of this research is to determine language test models in the translation subject based on Jean Piaget's theory, particularly in the fourth stage, which is formal operational practical operations. It aims to assess the progress in translation studies and proficiency in both the mother tongue and the target language. This research employs a literature review design and thematic method. The methodology involves literature research based on books and relevant literature related to translation examinations, such as Al-Khawli's book titled 'Ikhtibarat Al-Lughowiyah', along with various other related books and literature. Data collection techniques involve a literature review, including gathering books, journal articles, and previous relevant studies related to the research topic. These materials are then analyzed using Jean Piaget's theory. The results of this research provide various examples of translation examination models specifically designed for students aged 11 and above, meeting the current educational needs.